Immunosuppression and Immunomodulation 2023
DOI: 10.5772/intechopen.107362
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Immunosuppression in Patients with Diabetes Mellitus

Abstract: Diabetes is an age-dependent health issue prevalent worldwide and specially seen in those families with prevalent history of the disorder. Insufficient insulin production by the defective pancreas that leads to high blood glucose levels in the systemic circulation makes the patients more prone to an infection that exaggerates with time as compared to their counterparts. This increased prevalence of infections in diabetics may be due to defects in the immune functionality of the diabetes patients. High blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Numerous studies have revealed that people with diabetes are more likely to develop lower respiratory tract illnesses, such as pneumonia, urinary tract infections, pulmonary tuberculosis (TB), and infections of the skin and internal organ tissues. 11 Development of Otitis externa with conjunction of chickenpox in our patient may state that chickenpox can give rise to development of various complication as generally cause of otitis externa are bacterial infections as Pseudomonas aeruginosa and Staphylococcus aureus. 15 Antivirals should be administered as soon as possible to immunocompromised people and anyone who appears to be developing severe varicella for the best results.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Numerous studies have revealed that people with diabetes are more likely to develop lower respiratory tract illnesses, such as pneumonia, urinary tract infections, pulmonary tuberculosis (TB), and infections of the skin and internal organ tissues. 11 Development of Otitis externa with conjunction of chickenpox in our patient may state that chickenpox can give rise to development of various complication as generally cause of otitis externa are bacterial infections as Pseudomonas aeruginosa and Staphylococcus aureus. 15 Antivirals should be administered as soon as possible to immunocompromised people and anyone who appears to be developing severe varicella for the best results.…”
Section: Discussionmentioning
confidence: 69%
“…It is essential for the development of cutting-edge therapies to treat infections in diabetic patients and enhance treatment outcomes to have a deeper understanding of the mechanisms of hyperglycemia that compromise host defence against pathogens. 11 There are evidence indicating that an immunocompromised state occurs only in the context of poor glycemic control with severe complications. 12 Low production of interleukins in response to infection and hyperglycaemia both increase some pathogens' virulence; decreased chemotaxis, decreased phagocytic activity, and immobilization of polymorphonuclear leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies conducted on diabetic animals revealed that insulin deficiency resulted in immunosuppressive effects, which were evident through the impairment of macrophage phagocytosis and cytokine production. These effects were subsequently restored upon administration of insulin [ 34 , 35 , 36 ]. In vivo depletion of macrophages using clodronate liposome treatments has been shown to suppress various experimental inflammatory diseases [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%